PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 15 PANGKALAN NYIRIH - Justia Justia; Lazim N Lazim N; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is motivated by the low of science learning result of fourth grade students of SD Negeri 15 Pangkalan Nyirih with average value 62,88 (KKM 70). Of the 26 students only 10 students (38.46%) reached the KKM, and the remaining 16 students (61.54%) did not reach the KKM. The purpose of this research is to improve the science learning outcomes of fourth grade students of SD Negeri 15 Pangkalan Nyirih, with the application of Inquiry learning model. Teacher activity increased, in the first meeting of the I-cycle of teacher activity average 79.16% with the category of "good", the second meeting of the average teacher activity increased to 83.33% with the category "Very good". At the third meeting of the second cycle of the average teacher activity 87.50% with the category "Very good" and at the fourth meeting with an average activity of 91.66% also with the category "very good". While meeting I cycle-I average student activity 66,66% "good" category, at meeting of 2 mean of student activity increased to 70,83% with category "good". At the 3rd meeting of the II cycle the average student activity 75.00% with the category of "good" and at the 4th meeting has increased with the average student activity 79.16% also with the category of "good". Student learning outcomes on preliminary data above KKM only 10 people (38.46%), after the I-cycle increased as many as 20 people (77%) and after the second cycle increased again as many as 21 people (81%), the value the average obtained by students classically in the initial data only 62.88 after the first cycle increased by an average of 74.03 and in the second cycle more up to 81.34. From this research can be concluded that with the application of inquiry learning model can improve science learning outcomes of fourth grade students of SD Negeri 15 Pangkalan Nyirih.Keywords: Inquiry, science learning outcomes